Efeito do revestimento de quitosa na vida útil de filés de pargo (Lutjanus purpureus) armazenamento sob congelamento - Nunes, Eveline Maria Silveira (2014)
Consumers’ preference for minimally processed foods and their demand for quality have led to the development of films and coatings serving as a protective barrier to food. Since fish contain oxidizable fat, application of these coatings for product antioxidants may be beneficial. This work was evaluate the effectiveness of chitosan coating on shelf-life extension of fillets of snapper (Lutjanus purpureus), considering the microbiological and physico-chemical conditions and compare it with the traditional method of glazing. Fillets of snapper (Lutjanus purpureus) were obtained fresh and immediately frozen in the laboratory. After freezing a group of samples was water glazed (Treatment I), another group received chitosan coating (Treatment II) and the other received no treatment (Control). Following treatments, each fillet was individually packaged in polyethylene bags and subjected to frozen storage at a temperature of -18 °C ± 1 ° C for 180 days. Microbiological and physicochemical analyzes were performed every 30 days. Apart from Pseudomonas spp. and coagulase positive staphylococci bacteria, chitosan coating did not show any bactericidal or bacteriostatic effect on other microorganisms studied. In relation to the physicochemical quality analysis it was observed that during the 180 days of storage, the values of BVT showed no major changes. On the other hand, the TMA values increased significantly in the last days of storage for all groups. The pH values increased significantly only in the control group over the period of frozen storage while the TBARS values indicated that either chitosan coating or water glazing clearly inhibited lipid oxidation in fish fillets during storage. The color analyses indicated that the samples treated with both coatings showed minor changes on both skin and muscle, compared to the control, probably due to the protection provided by these layers. Regarding to texture analyses, there was a slight reduction of the shear force of the samples in all groups; however these values were not statistically different. It is concluded that the chitosan coating helped to prevent lipid oxidation and color changes in the skin and muscle of fish, maintaining the pH, and yet there was a beneficial effect of this coating on its microbiological quality thus, contributing to extend the shelf life of frozen red snapper fillets.